FORWARD AND INVERSE MODELING 2D SELF-POTENTIAL METHOD BASED ON CONTINUOUS GEOMETRY BY USING FINITE DIFFERENCE METHOD AND WEIGHT LEAST-SQUARE METHOD - Triyandi (NIM: 10213097), Cecep
Geophysics is one of the science that discusses the physical properties of the earth by analyzing the subsurface conditions and physical parameters of rocks in the earth. One of the geophysical methods used in this research is the Self-potential (SP) method which is one of the passive geophysical methods (no electric current injection) for measuring the potential difference between two points on the surface of the earth. In this final project, SP analysis of the measured anomaly of future modeling and inversion modeling results was performed. Future modeling represents a subsurface condition that produces a surface response which is assumed as a measured SP anomaly data. The method is based on continuous geometry which is approximated by solving Poisson equations using finite difference (FDM) method. The resulting results show potential anomalies beneath the surface according to the natural source test model. In the inversion modeling, the response data for future modeling results is used to generate the source model parameters at. This inversion modeling uses weight least-square method to minimize the number of model vector length. The inversion results show the repson matching the observed data.